Adaptive Public Administration and Policy Making in the Context of Globalization, Technology, and International Organizations - Basyo, Irfan; Ilham, Andi; Daud, Agum (Journal Social Civilecial, 2023)
This paper aims to fill the gap in the literature by studying the effects of globalization on PA and the policy-making process, with specific reference to the role of IOs, technology, TAs and other actors. This research explored the nature of global public administration through the use of multiple case studies, semi-structured interviews of policymakers and practitioners, and document review. The study also shows that transnational actors including and especially the UN and the IMF are powerful political actors that can shift national policies in developing countries by offering loans, advice, and policy prescriptions. Additionally, technology takes the central position as a driver of change making processes in PAS, e-government initiatives such as online public services increase transparency, efficiency and citizens’ participation. Furthermore, the study reveals trends and patterns of networked governance that refers to collective efforts of governments, organizations, companies, and civil society in managing multifaceted global challenges. When embodying these ideas, these observations compensate for the existing shortages in the literature by providing a systematic understanding of how different globalization presupposes governance adaptability and inclusiveness. As a result, it is argued that public administration in the conditions of the modern globalization process needs innovative leadership, diverse stakeholders’ cooperation, and focus on ethical sense in terms of uncertainty and variety of the global world. The findings of this study are important to policy makers concerned with building strong and adequate public administration for responding to the challenges arising from globalization.